Influence of Image Media on Public Elementary School Students' Reading Interests - Widayanti, Rekha Ardillah; Fitri, Riskal; Irviana, Ira (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study intends to determine the effect of image media on the reading interest of Class II students of public elementary schools. The research method used is quantitative research with a descriptive approach by experimental method. The research sample consisted of 30 class II students of public elementary school Tabaringan 5 Makassar. We obtained data from the study using questionnaires, specifically pretests and posttests. Data analysis uses normality analysis and hypothesis testing. We used the t-test to independently determine the significance of the independent variable (X) on the dependent variable (Y). The findings showed an increase in the average value from the pretest of 60.50 to 77.50 in the posttest after the use of image media. Additionally, regression analysis and hypothesis testing showed that image media had a positive and significant influence on students' reading interest, with a coefficient of determination (R²) of 0.687. This study proves that the use of image media can significantly increase students' reading interest. Image media has proven to be effective as a learning aid in fostering students' motivation and interest in reading activities in lower grades.